Juridical Review of Notary Positions Based on the Law on Notary Positions in Welfare Aspects - Adyesha Nur Salma; Taufan Fajar Riyanto; Ira Alia Maerani (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
Notary as a public official who is not paid, either by the state, ministry, or any other party according to UUJN. Sociologically, notaries are stigmatized as one of the respectable professions in society. On the other hand, the presence of a notary in the community has also increased in quantity, so that it is correlated with competition in the task of a notary.This study aims to determine and analyze the responsibilities of a notary in carrying out the position of a notary, to find out and analyze the role of the Indonesian Notary Association in implementing the welfare of a notary in the city of Semarang, and to find out an example of a Sale and Purchase Binding Agreement. The research approach method used in this thesis is an empirical juridical legal research method with descriptive analysis research specifications.Data sources and data collection methods used primary and secondary data which were analyzed qualitatively.The results showed that: First,The position of a notary in Article 1 point 1 UUJN, namely a public official authorized to make authentic deeds and other authorities as referred to in the law. While the term public official is translated from openbare ambtenaren as in Article 1868 of the Civil Code that,